Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Cumulative Review: 8

Answer

$2-x$

Work Step by Step

$\frac{x^{2}-4x+4}{2-x}$ =$\frac{x^{2}-2x-2x+4}{-x+2}$ =$\frac{x(x-2)-2(x-2)}{-1(x-2)}$ =$\frac{(x-2)(x-2)}{-1(x-2)}$ =$\frac{(x-2)}{-1}$ =$-(x-2)$ =$-x+2$ =$2-x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.